2021
DOI: 10.2147/hiv.s328643
|View full text |Cite
|
Sign up to set email alerts
|

Social Networks and Barriers to ART Adherence Among Young Adults (18–24 years) Living with HIV at Selected Primary Health Facilities of South-Western Uganda: A Qualitative Study

Abstract: Background: Young adults living with HIV (YALWH) struggle to maintain high levels of adherence to antiretroviral therapy (ART) because of numerous barriers. This study describes the social networks of YALWH (18-24 years), their barriers to ART adherence, and the perceived role of social networks in overcoming those barriers. Methods: This study used a qualitative descriptive research design. Twenty-three (23) YALWH who were on ART for a period of greater than one (1) month and had consented to participate in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 74 publications
1
7
0
Order By: Relevance
“…These results are plausible because all these are critical external factors that disturb HIV-positive clients psychologically to appoint where they may become non-adherent to their drugs hence unsuppressed viral load due to forgetfulness, anger, and fear of taking their drugs on an empty stomach. Our studies are similar to the results of previous studies conducted in Uganda, 19,20 Eswatini, 18 and a systematic review on barriers and facilitators to ART adherence in sub-Saharan Africa 21 which showed that stigma and discrimination, shortage of food, delayed viral load results, and heavy workload can lead to non-adherence to ART hence unsuppressed viral load. We encourage HIV service providers to avail viral load results to HIV-positive clients as soon as they are ready so that they may know whether what they are currently doing to remain on treatment is working.…”
Section: Opportunity-related Barriers To Successful Iacsupporting
confidence: 90%
“…These results are plausible because all these are critical external factors that disturb HIV-positive clients psychologically to appoint where they may become non-adherent to their drugs hence unsuppressed viral load due to forgetfulness, anger, and fear of taking their drugs on an empty stomach. Our studies are similar to the results of previous studies conducted in Uganda, 19,20 Eswatini, 18 and a systematic review on barriers and facilitators to ART adherence in sub-Saharan Africa 21 which showed that stigma and discrimination, shortage of food, delayed viral load results, and heavy workload can lead to non-adherence to ART hence unsuppressed viral load. We encourage HIV service providers to avail viral load results to HIV-positive clients as soon as they are ready so that they may know whether what they are currently doing to remain on treatment is working.…”
Section: Opportunity-related Barriers To Successful Iacsupporting
confidence: 90%
“…Young adolescents (10–15 years) and older adolescents (15–17 years) face adherence challenges due to developmental changes and leading to an inability to undertake the task of their HIV management [ 35 ]. Factors such as dependence on parents, guardians, family settings for medication administration, keeping clinic appointments, disclosure of HIV-positive status, attending school, type and dosing of ARV, and patient-provider relationship may adversely affect their adherence to ART, leading to ART failure and/ or development of drug resistance [ 35 , 36 ]. Determinants of adherence and treatment failure in young adults (18–24 years) include self-stigma, non-disclosure of HIV-positive status to family members and sexual partners, age-related behaviors such as alcoholism, illegal drug abuse and transitioning from adolescence to adult HIV care [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…patient-provider relationship may adversely affect their adherence to ART, leading to ART failure and/ or development of drug resistance [35,36]. Determinants of adherence and treatment failure in young adults (18-24 years) include self-stigma, non-disclosure of HIV-positive status to family members and sexual partners, age-related behaviors such as alcoholism, illegal drug abuse and transitioning from adolescence to adult HIV care [36].…”
Section: Plos Onementioning
confidence: 99%
“…This implies that losing or having a male breadwinner suffering from HIV/AIDs can result in a significant loss of income and time for men, which can negatively impact their ability to grow and thrive compared to women. A study by Ajuna et al 51 in Uganda found that households with HIV‐positive women had lower income and expenditure levels compared to households with HIV‐negative women. However, the study also found that households with HIV‐positive men had higher income and expenditure levels compared to households with HIV‐negative men.…”
Section: Discussionmentioning
confidence: 99%